2015
DOI: 10.1128/jvi.03105-14
|View full text |Cite
|
Sign up to set email alerts
|

COMMD1/Murr1 Reinforces HIV-1 Latent Infection through IκB-α Stabilization

Abstract: The transcription factor NF-B is important for HIV-1 transcription initiation in primary HIV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…NELFA is a component of the NELF complex restricting transcription elongation at the LTR promoter in absence of Tat (Karn and Stoltzfus, 2012). COMMD1 is an HIV-1 restriction factor in primary resting CD4 lymphocytes (Ganesh et al, 2003) and can reinforce HIV-1 latency by attenuating NF-κB signaling in myeloid cells (Taura et al, 2015). Another potential identified upstream regulators, Transforming Growth Factor, Beta Receptor 1 (TGFBR1) is also interesting since the mTOR pathway is a downstream effector of TGF-β signaling and an upstream regulator of actin remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…NELFA is a component of the NELF complex restricting transcription elongation at the LTR promoter in absence of Tat (Karn and Stoltzfus, 2012). COMMD1 is an HIV-1 restriction factor in primary resting CD4 lymphocytes (Ganesh et al, 2003) and can reinforce HIV-1 latency by attenuating NF-κB signaling in myeloid cells (Taura et al, 2015). Another potential identified upstream regulators, Transforming Growth Factor, Beta Receptor 1 (TGFBR1) is also interesting since the mTOR pathway is a downstream effector of TGF-β signaling and an upstream regulator of actin remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…Induction of cOMMd1 in HIV-1 latent-infected cells also maintains latent HIV-1 infection. The expression of the cOMMd1 protein and mRNA in HIV-1 latent-infected myeloid cells is stronger than in parental cells (10). However, it remains elusive how cOMMd1 transcription and expression are regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that, in addition to activating NF-κB p65 itself, p53 expression assists and is involved in NF-κB p65-driven reactivation of HIV-1 latently infected U1 cells. An increased expression of PARP is required for the activation of NF-κB-dependent target genes, including HIV-1 LTR in reporter constructs; a decreased expression of COMMD1 reinforces HIV-1 latent infection through IκBα stabilization [22].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the host-derived factor, COMM Domain-containing protein 1 (COMMD1), is able to reinforce HIV-1 latent infection through IκB-α stabilization in U1 cells, which inhibits HIV-1 replication by blocking NF-κB p65 activities in initiation of HIV-1 transcription [22]. To investigate whether p53 had an effect on expression of COMMD1 protein, U1 cells 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway is involved in the maintenance of HIV-1 latency, inhibition of the pathway can reactivate HIV-1 replication from its latent infection [18].…”
Section: P53 Expression Suppressed Commd1 Expression and Promoted Parmentioning
confidence: 99%